AUDIT OF FOREIGN ECONOMIC ACTIVITIES IN THE SUSTAINABLE DEVELOPMENT MANAGEMENT SYSTEM OF AN ENTERPRISE (INNOVATIVE ECONOMY, 2025)
Kashchena N.B., Yatsiuk О.V., Bogomaz О.P.  AUDIT OF FOREIGN ECONOMIC ACTIVITIES IN THE SUSTAINABLE DEVELOPMENT MANAGEMENT SYSTEM OF AN ENTERPRISE Purpose. The aim of the article is to substantiate the theoretical foundations and organizational and methodological aspects of the audit of foreign economic activity (FEA) as a component of the information system for managing sustainable development of an enterprise.Methodology of research. The following methods were used in this article to achieve this goal and fulfil the outlined tasks: analysis and synthesis – to identify the components of the information system for managing the sustainable development of an enterprise and substantiate the theoretical foundations of the FEA audit; systematic approach – to develop organizational and methodological aspects of the FEA audit; generalization – to adapt international audit standards to the specifics of FEA and determine their role in managing sustainable development; integrated approach – to formulate recommendations for integrating audit results into the strategic plan.Findings. The theoretical basis for auditing foreign economic activity, which combines risk-oriented and integrated approaches, integration of ESG criteria and reduction of information asymmetry, is substantiated. The organizational and methodological principles of audit are proposed, covering all modules of the information system for managing the sustainable development of an enterprise, and involving the application of international reporting and auditing standards, the latest digital solutions and analytical platforms. Recommendations for integrating audit results into strategic management through risk management, automation and ESG initiatives, as well as communication with stakeholders through transparent reporting and digital channels are formulated.Originality. An integrated approach to auditing foreign economic activity as a cross-cutting element of the sustainable development management information system that integrates financial, environmental and social aspects was developed. The audit methodology was improved by taking into account ESG criteria, risk orientation and digital tools, which meets the current challenges of European integration.Practical value. The developed recommendations allow enterprises to increase the efficiency of foreign economic activity, reduce risks, ensure compliance with international standards and strengthen stakeholder confidence. The introduction of automation and ESG initiatives contributes to competitiveness and sustainable development in the global market.Key words: foreign economic activity audit, sustainable development, information system, ESG criteria, risk-based approach, integrated reporting, strategic management, stakeholders.
Keywords: foreign economic activity audit; sustainable development; information system; ESG criteria; isk-based approach; integrated reporting; strategic management; stakeholders